The Omani Distance Learning Program to Teach the Holy Quran: Analytical Descriptive Study - Al-Musawi, Ali Sharaf; Al Akhzami, Salim; Al Hinai, Abdullah (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractThis study aimed to investigate the usefulness of Omani distance-learning program to teach the Holy Quran and identify its advantages and disadvantages as viewed by the program stakeholders (administrators, teachers, students). The study used both analytical and descriptive approaches. The study sample was selected using purposive sampling to be representative of the study community of administrators, teachers and students. A survey questionnaire, consists of 19 statements, was designed and measured to ensure its validity and reliability. The findings indicated high satisfaction among the stakeholders on most items of the questionnaire with regard to the educational components of the program with a mean score of 4.16. Additionally, the findings showed that there was no statistically significant difference between the stakeholders’ views in terms of the gender, both male and female, variables. The study recommended that the program administrators should work to enhance the positive aspects of the program highlighted by the study and to avoid the passivity emerged from the study..AbstrakPenelitian ini bertujuan menyelidiki kegunaan program pembelajaran jarak jauh di Oman untuk mengajarkan Al-Quran dan untuk mengidentifikasi kelebihan dan kekurangan yang dilihat oleh para pemangku kepentingan program (administrator, guru, siswa). Penelitian ini menggunakan pendekatan analitis deskriptif. Sampel penelitian dipilih menggunakan purposive sampling untuk mewakili komunitas studi dari administrator, guru dan siswa. Kuesioner survei yang terdiri dari (19) pernyataan dirancang dan diukur untuk memastikan validitas dan reliabilitasnya. Temuan menunjukkan kepuasan yang tinggi di antara para pemangku kepentingan pada sebagian besar item kuesioner berkenaan dengan komponen pendidikan program dengan skor rata-rata (4,16). Selain itu, temuan menunjukkan bahwa tidak ada perbedaan yang signifikan secara statistik antara pandangan para pemangku kepentingan dalam hal variabel gender (pria / wanita). Studi ini merekomendasikan bahwa administrator program harus bekerja untuk meningkatkan aspek positif dari program yang disorot oleh penelitian dan untuk menghindari kepasifan yang muncul dari penelitian. How to Cite : Al Akhzami, S., Al Hinai, A., Al Musawi, A. (2019). The Omani Distance Learning Program to Teach the Holy Quran: Analytical Descriptive Study. TARBIYA: Journal of Education in Muslim Society, 6(1), 1-9. doi:10.15408/tjems.v6i1.11182.